IbM Guru SD dalam Pembuatan Media 3D untuk Pengajaran Bahasa Inggris - Qomariah, Siti Syafi’atul; Permana, Dira; Nafisah, Baiq Zuhrotun (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This IbM program aimed to help teachers of both schools in making application of 3D especially in English learning. This program was conducted at SDN 1 Langko and SDN 2 Langko Janapria Central Lombok. SDN 1 Langko had 12 teachers, 94 students and 1 staff, then SDN 2 Langko had 12 teachers, 240 students and 1 staff. The steps which was conducted were requirement (determined tools), designing, coding, testing and implementing. The result of this public services was application which could be used by English teachers in improving quality of students’ learning.